2021
DOI: 10.18632/aging.203228
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory patterns of blood pressure change up to six years and the risk of dementia: a nationwide cohort study

Abstract: The present study aimed to investigate the associations between the trajectory of blood pressure (BP) change and the risk of subsequent dementia and to explore the differences in age, gender, and hypertension subgroups. We included 10,660 participants aged ≥ 60 years from 1998 to 2018 waves of the Chinese Longitudinal Healthy Longevity Survey. Latent growth mixture models were used to estimate BP trajectories. Cox-proportional hazard models were used to analyze the effects of BP trajectories on the risk of dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Similar to our study, a cohort study of the elderly with a median age of 77 years conducted in the United States identified trajectories of increased, little changed, and declined SBP by hierarchical cluster analysis (Smitson et al, 2017). Cheng et al (2021) also demonstrated four unique BP/PP trajectories: normal, stabilized, elevated, and persistently high BP/PP in the Chinese elderly. In previous studies, the differences in the baseline characteristics and risk of heart disease and cerebrovascular disease among BP/PP trajectory groups were similar to our study (Smitson et al, 2017;Cheng et al, 2021).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Similar to our study, a cohort study of the elderly with a median age of 77 years conducted in the United States identified trajectories of increased, little changed, and declined SBP by hierarchical cluster analysis (Smitson et al, 2017). Cheng et al (2021) also demonstrated four unique BP/PP trajectories: normal, stabilized, elevated, and persistently high BP/PP in the Chinese elderly. In previous studies, the differences in the baseline characteristics and risk of heart disease and cerebrovascular disease among BP/PP trajectory groups were similar to our study (Smitson et al, 2017;Cheng et al, 2021).…”
Section: Discussionsupporting
confidence: 83%
“…Cheng et al (2021) also demonstrated four unique BP/PP trajectories: normal, stabilized, elevated, and persistently high BP/PP in the Chinese elderly. In previous studies, the differences in the baseline characteristics and risk of heart disease and cerebrovascular disease among BP/PP trajectory groups were similar to our study (Smitson et al, 2017;Cheng et al, 2021). Thus, the occurrence of lowered BP in our study should not be considered a complication of heart disease and cerebrovascular diseases.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Three 30 or four 31 different PP trajectories were observed by different studies using GBTM, which allowed identification of distinct patterns of PP change as independent trajectory groups. The specific number of classes may be linked to the age range, follow‐up period and the number of studied samples 32 .…”
Section: Discussionmentioning
confidence: 99%
“… 31 Steep declines in BP preceding onset of dementia or clinical diagnosis of Alzheimer’s disease were also observed in the Kungsholmen project 32 , 33 and in those over 78 years in the Adult Changes in Thought Study ( n = 2356). 34 Cheng et al 35 calculated that the risk of developing dementia was highest when hypertension was ‘stabilized’ and lowest in participants with normal BP who developed hypertension over the 6-year study period. In very late life, hypertension is protective against dementia.…”
Section: Introductionmentioning
confidence: 99%